Metal-doped carbon nanoparticles with intrinsic peroxidase-like activity for colorimetric detection of H2O2 and glucose. Issue 2 (13th December 2018) - Bao, Yan-Wen; Hua, Xian-Wu; Ran, Huan-Huan; Zeng, Jia; Wu, Fu-Gen
Abstract : We develop a general hydrothermal approach to fabricate new nanozymes with intrinsic peroxidase-like activity for H2 O2 and glucose detection. Abstract : Nanomaterial-based enzyme mimics (nanozymes) are attracting increasing attention because of their low production cost, high stability against denaturation, and resistance to high concentrations of substrates. Here, carbon nanoparticles doped with a small amount (<5 mol%) of Pt (denoted as PtCNPs) are synthesized via a facile, cost-effective hydrothermal treatment of p -phenylenediamine (PPD) and K2 PtCl4 . The obtained PtCNPs possess high aqueous stability, excellent water-dispersibility, and suitable size (∼15 nm). More interestingly, the PtCNPs exhibit an intrinsic peroxidase-like activity that can quickly catalyze 3, 3′, 5, 5′-tetramethylbenzidine (TMB) in the presence of hydrogen peroxide (H2 O2 ) and produce a blue color. Importantly, since satisfactory catalytic properties were also observed when K2 PtCl4 was replaced with CuCl2, NiCl2, or Na2 PdCl4 during the synthesis, the PPD- and inorganic metal salt-involved hydrothermal synthetic approach may be developed as a general and simple way to fabricate new nanozymes. Besides, the steady-state kinetics reveals that the PtCNPs have a stronger affinity for TMB and a weaker affinity for H2 O2 compared with horseradish peroxidase. On the basis of the color reaction, a colorimetric detection method for H2 O2 and glucose has been successfully established with a detection limit of 0.15 and 0.30 μM, respectively. Further, the method has also been successfully applied for glucose detection in human serum samples. To sum up, this work develops a new synthetic method of metal-doped carbon nanomaterials and demonstrates their capability for the sensitive and selective detection of H2 O2 and glucose, which may foster the development of new nanozymes for biosensing applications.